Characterization of soils cultivated with rubber in the Colombian Bajo Cauca Antioqueño region (2017)
From a socioeconomic and environmental standpoint, rubber cultivation is potentially important for Colombia, because it not only constitutes an alternative to the traditional mining, agricultural, and livestock activities, but also a beneficial option in the substitution of illegal crops. Thus, there is need to determine the factors restricting the productivity of the species, particularly soil-related aspects. In this context, the current research undertook the description and identification of soil physical and chemical properties in three rubber plantations located in a region known as Bajo Cauca Antioqueño, at the lower course of the Cauca river. The results indicate that these soils are classified as Ultisols, they are deep, with acid reaction and low levels of soil organic matter. Essential elements also exhibited low levels, except Cu. Fe and Al are also present in very high concentrations, while the cation exchange capacity is limited. These observations alert on the need for agronomic management techniques that allow the crop to express its full potential under conditions that are not very adequate for its growth and development